Pendampingan Berkelanjutan Dalam Upaya Peningkatan Pengetahuan Bionomik Vektor Malaria Guna Pencegahan Malaria - Mulyani, Wiwiek; Mofu, Renold Markus; Natalia, Yeyen Fien (SEGANTANG LADA : JURNAL PENGABDIAN KESEHATAN, 2024)
Malaria remains a serious health problem in Keerom District, Papua Province, with an Annual Parasite Incidence (API) of 368 per 1000 population in 2018. This community service activity aims to improve the knowledge of malaria cadres about vector bionomics and skills in making insecticide-treated bed nets in Jaifuri Village. The method used is counselling with flipchart media and a demonstration of making insecticide-treated bed nets. The activity was carried out on July 4, 2024, involving 12 malaria cadres and related stakeholders. The pre-test and post-test results showed a significant increase in knowledge; whereas before counselling, 80.66% of participants had low knowledge, but after counselling, 100% reached the good knowledge category. This activity also improved cadres' skills in making insecticide-treated bed nets, which are essential to malaria prevention. It can be concluded that this community service activity effectively increases the capacity of malaria cadres as the frontline in malaria control efforts at the community level.